CTNI-36. INITIATION OF A PHASE 1 DOSE-ESCALATING STUDY OF WEEKLY DIRECT-TO-BRAIN ADMINISTRATION OF SOLUBILISED FORMULATION OF PANOBINOSTAT (MTX110) IN PATIENTS WITH RECURRENT GLIOBLASTOMA (MAGIC-G1 STUDY). (14th November 2022) - Desjardins, Annick; Conlon, Kelly; Gunning, Hannah; Davies, Rhian; Komisarow, Jordan; Cavaliere, Robert; Zamoryakhin, Dmitry
Abstract: INTRODUCTION: Glioblastoma (GBM) is the most aggressive primary brain tumour in adults, leading to universal recurrence despite aggressive surgical and chemotherapeutic treatment. Post-recurrence, median overall survival is 6 to 10 months and treatment options are very limited. One of the biggest challenges in treating GBM is achieving high local drug concentration; systemic administration of cytotoxic agents has failed in the past due to this limitation. Convection enhanced delivery (CED) is a 'direct-to-brain' drug delivery method that previously demonstrated its usefulness in overcoming this challenge. MTX110 (Midatech Pharma Ltd) is a water-soluble form of panobinostat, that demonstrated cytotoxic activity in 4 GBM cell lines (U87MG, U251MG, U118MG and T98G) with an average IC50 value around 40nM which also translated into pre clinical in vivo efficacy, in combination with radiotherapy 1 . Delivery of MTX110 via an implanted pump and CED catheter system in patients with GBM appears to be an attractive treatment option, that allows for therapeutic doses of the drug to be delivered weekly directly to the tumour, thus avoiding systemic administration and therefore toxicity. This has previously been demonstrated in investigator-initiated studies of paediatric patients with diffuse intrinsic pontine glioma. METHOD: MAGIC-G1 study is a Phase 1 two-cohort dose-escalating study that will assess safety and feasibility of intermittent intratumoral administration of MTX110 by CED to rGBM patients; either as a single agent (Cohort 1) or in combination with lomustine (Cohort 2). Eligible patients will have a catheter system and an abdominal refillable pump implanted in an aseptic manner, with the tip of the catheter positioned stereotactically at the centre of the tumour. 48-hour infusions will be administered weekly until disease progression and doses of 30, 60 and 90 mM will be investigated. Cohort 1 recruitment will be completed before Cohort 2 starts dosing. Study results are expected in 2023.